Evaluation of a novel cardiac signal processing system for electrophysiology procedures: The PURE EP 2.0 study. - Al‐Ahmad, Amin; Knight, Bradley; Tzou, Wendy; Schaller, Robert; Yasin, Omar; Padmanabhan, Deepak; Zagrodzky, Jason; Bassiouny, Mohammed; Burkhardt, J. David; Gallinghouse, G. Joseph; Mansour, Moussa; McLeod, Christopher; et al. (Journal of Cardiovascular Electrophysiology, 2021)
Background: Intracardiac electrogram data remain one of the primary diagnostic inputs guiding complex ablation procedures. However, the technology to collect, process, and display intracardiac signals has known shortcomings and has not advanced in several decades. Objective: The purpose of this study was to evaluate a new signal processing platform, the PURE EP™ system (PURE), in a multi‐center, prospective study. Methods: Intracardiac signal data of clinical interest were collected from 51 patients undergoing ablation procedures with PURE, the signal recording system, and the 3D mapping system at the same time stamps. The samples were randomized and subjected to blinded, controlled evaluation by three independent electrophysiologists to determine the overall quality and clinical utility of PURE signals when compared to conventional sources. Each reviewer assessed the same (92) signal sample sets and responded to (235) questions using a 10‐point rating scale. If two or more reviewers rated the PURE signal higher than the control, it was deemed superior. Results: A total of 93% of question responses showed consensus amongst the blinded reviewers. Based on the ratings for each pair of signals, a cumulative total of 164 PURE signals out of 218 (75.2%) were statistically rated as Superior for this data set (p <.001). Only 14 PURE signals out of 218 were rated as Inferior (6.4%). Conclusion: The PURE intracardiac signals were statistically rated as superior when compared to conventional systems.